Incidencia de la lectura en la destreza de escribir en los estudiantes de segundo año de bachillerato general unificado, paralelos “A”, “B” y “E” de la unidad educativa anexa a la Universidad Nacional de Loja, año lectivo 2013- 2014 - Armijos Cabrera, Julia Edith (2015)
This research work entitled "Incidence of reading skills in writing sophomores Unified School General parallel" A "," B "and" E "of the Education Unit Attached to the National University Loja, school year 2013-2014 ", pose general objective: Contribute to the development of language and literature macrodestrezas investigating how this affects reading skills writing students sophomore year Unified General parallel " A " , "B" and "E", for which methods were used: scientific, inductive, deductive, analytical, synthetic; as technical literature, statistics, and an instrument the questionnaire. The main result obtained is that: social networks, video games, the Internet, are the main reasons why students do not spend time reading. Besides the activities proposed by teachers do not favor the development of the reading habit, also at home parents they do not motivate them to read and causes their children do not take interest in reading, and this is reflected in the writing skill. We conclude that a significant impact on reading skills writing, because people who practice reading skills have better expression, improve spelling and grammar, vocabulary expanded further; so it is recommended reading workshops within the school, involving teachers, parents and students to recognize the importance this has on their education.